Bahasa Inggris - Afrilihadi, Achmad Robi; Sumadi, Tjipto; Nadiroh, Nadiroh (Journal of Moral and Civic Education, 2025)
Schools function as civic laboratories by utilizing digital technology to instill national values in students, enabling them to promote local culture and traditions through digital media and contribute to a modern national algorithm. This study identifies strategies for integrating digital technology into Pancasila education and examines the role of schools in shaping this national algorithm via social media. Using a systematic literature review, the research focuses on technology-driven citizenship education in the digital era. Findings indicate that schools integrating digital technology into civic education significantly enhance students' understanding of national values. Generation Z actively participates in digital-based civic activities, spreading regional culture, language, and traditions through social media. Teachers, as facilitators of digital citizenship, play a crucial role in shaping students' national identities, particularly in schools with strong technological access. Students receiving digital-based civic education are more proactive in sharing nationalistic content, fostering a national algorithm that boosts national and state awareness among social media users.This research offers practical implications for educators, serving as a guide for integrating digital technology into civic education to develop a national algorithm. It also provides a fresh perspective for Indonesian education policy, advocating the inclusion of digital citizenship in the civic education curriculum to address the challenges and opportunities of the digital era.